Profil HbA1c, Kolesterol dan Trigliserida pada Pasien Diabetes Mellitus Tipe 2 - Gunardi Gunardi (Jaringan Laboratorium Medis, 2020)
Diabetes mellitus type 2 (DM Type-2) is a metabolic disease which characterized by hyperglycemia due to failure of insulin secretion, insulin action or both. If DM is not handled properly, then it will arise complications in various organs of the body. The criterias of DM control including HbA1c levels and lipid fractions. Lipid pattern in patients with DM type 2 is very dependent on HbA1c control. High HbA1c is associated with high triglycerides and cholesterol. Research objectiveÂ to find out the description of Hba1c, cholesterol and triglyceride levels in patients of DM type 2 at the Outpatient Poly of RSUD Tidar Magelang. Research methodÂ the research type was descriptive with observational design. Primary data were obtained from levels measurements of HbA1c, cholesterol and triglycerides.. The normal HbA1c levels 4-5,80%, good control 6,1-6,5%, moderate 6,6-7,8%, bad 8,8-14,1% respectively as much as 65,96%, 12,77%, 10,64%, and 10,90%. The normal cholesterol levels 100-160 mg/dL, moderate 200-220 mg/dL, and high 250-300 mg/dL, respectively 74,47%, 10,64%, and 14,89%. The normal triglyceride levels 70-140 mg/dL, high limit 150-165 mg/dL, and high 200-252 mg/dL respectively as much as 63,83%, 19,15% and 17,02%. Based on the age of normal HbA1c levels as much as 65,96%, normal cholesterol 74,47%, and triglycerides 63,83%. The levels of HbA1c, cholesterol, and triglycerides were mostly normal in age groups of elderly, and male. The high levels of HbA1c, cholesterol, and triglycerides were more common in elderly than in other age groups.